(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the features of the use of cognitive technologies in connection with the need to move to a system of distance educational resources. In addition, the features of cognitive technologies in the context of distance learning will be characterized.